Enhanced electrocatalytic activity and stability of Pd3V/C nanoparticles with a trace amount of Pt decoration for the oxygen reduction reaction. Issue 42 (23rd September 2015) - Liu, Sufen; Han, Lili; Zhu, Jing; Xiao, Weiping; Wang, Jie; Liu, Hongfang; Xin, Huolin; Wang, Deli
Abstract : A trace amount of Pt decorated on the surface or inside of Pd3V/C nanoparticles significantly enhanced the ORR electrocatalytic activity and stability. Abstract : Carbon supported Pd3 V bimetallic alloy nanoparticles (Pd3 V/C) have been successfully synthesized via a simple impregnation–reduction method, followed by high temperature treatment under a H2 atmosphere. Electrochemical tests reveal that the half-wave potential of Pd3 V/C-500 shifts positively 40 mV compared with Pd/C. However, the catalytic activity of Pd3 V/C-500 suffers from serious degradation after 1k cycles. By a spontaneous displacement reaction or co-reduction method, a trace amount of Pt was decorated on the surface or inside of the Pd3 V/C nanoparticles. The catalytic activity and stability of the Pd3 V@Pt/C and Pt-Pd3 V/C catalysts for the oxygen reduction reaction (ORR) are enhanced significantly, and are comparable to commercial Pt/C. In addition, the Pt mass activity of Pd3 V@Pt/C and Pt-Pd3 V/C improves by factors of 10.9 and 6.5 at 0.80 V relative to Pt/C. Moreover, Pt-decorated Pd3 V/C nanoparticles show almost no obvious morphology change after durability tests, because the Pt-rich shell plays an important role in preventing degradation.